Xanthogranulomatous Pyelonephritis: Synchronous Upper and Lower Gastrointestinal Bleed - Muhammad Usman Mirza MBBS; John Van Taunay MD; Muhammad Waleed MBBS; Shiva Shankar Vangimalla MBBS; Sharana Hegde MBBS; Muhamad Alhaj Moustafa MD (SAGE Publishing, 2019)
Xanthogranulomatous pyelonephritis (XGP) is a rare chronic granulomatous destructive process of the renal parenchyma. It is caused by a chronic inflammatory process due to recurrent urinary tract infections and/or obstructing renal calculi. Rarely, it presents with advanced complications including abscesses and fistula formations. In this article, we report a unique presentation of XGP with simultaneous upper and lower gastrointestinal bleeding in the setting of XGP with reno-gastric and reno-colic fistulas.